Early response of the northeast subarctic Pacific plankton assemblage to volcanic ash fertilization. (9th January 2014) - Mélançon, Josiane; Levasseur, Maurice; Lizotte, Martine; Delmelle, Pierre; Cullen, Jay; Hamme, Roberta C.; Peña, Angelica; Simpson, Kyle G.; Scarratt, Michael; Tremblay, Jean-Éric; Zhou, Jie; Johnson, Keith; et al.
Abstract : Fe‐poor water collected at Sta. P20 in the Gulf of Alaska in June 2011 was enriched with different concentrations of volcanic ash (0.12, 1.2, and 10 mg L ‒1 ) from two subduction zone volcanoes, Kasatochi and Chaiten, and incubated onboard under in situ conditions for 6 d. The experimental setup also included a control (no addition) and a positive control (addition of 0.6 nmol L ‒1 FeSO4 ). Following a 4 d lag period, there were increases in carbon fixation rates (up to a factor of 10) and chlorophyll a concentrations (up to a factor of 3) in the positive control and in the ash‐enriched (1.2 and 10 mg L ‒1 ) treatments. Diatoms dominated at the end of the incubations, but cyanobacteria, dinoflagellates, pelagophytes, and haptophytes were also stimulated by the presence of ash. Deposition of ∼ 1 mg ash L ‒1, which is in the lower range of those estimated to have caused the August 2008 bloom following the eruption of the Kasatochi volcano in the Aleutian Islands, would suffice to trigger a bloom in the Gulf of Alaska.